Applied Clay Science - Applied Clay Science (Elsevier, 2026)
An International Journal on Physics, Chemistry, Geology and Technology of Clays and Clay Minerals. Applied Clay Science is an international journal attracting high-quality, novel scientific papers on clays and clay minerals, including research papers, reviews, and technical notes.
FI 1.19
Q2
Keywords: Geology; Geología; Acuerdos transformativos; Transformative agreements; Arcillas; Minerales; Contaminación; Aplicaciones geotécnicas